2021
DOI: 10.3389/fphar.2021.712181
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Potentiates the Effects of Anlotinib in NSCLC via AMPK/mTOR and ROS-Mediated Signaling Pathways

Abstract: Anlotinib is a novel multi-targeted tyrosine kinase inhibitor with activity against soft tissue sarcoma, small cell lung cancer, and non-small cell lung cancer (NSCLC). Potentiating the anticancer effect of anlotinib in combination strategies remains a clinical challenge. Metformin is an oral agent that is used as a first-line therapy for type 2 diabetes. Interesting, metformin also exerts broad anticancer effects through the activation of AMP-activated protein kinase (AMPK) and inhibition of mammalian target … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…For example, activating AMPK-mTOR-ULK1 reinforced autophagy, apoptosis, and cytotoxicity in human bladder cancer induced by10-hydroxycamptothecin [45]. The AMPK-mTOR axis took part in NSCLC treatment by inhibiting cell proliferation, migration, invasion, and glycolysis and activating oxidative stress, autophagy, and apoptosis [46][47][48][49]. In the present study, RSV activated AMPK and mTOR by phosphorylation.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…For example, activating AMPK-mTOR-ULK1 reinforced autophagy, apoptosis, and cytotoxicity in human bladder cancer induced by10-hydroxycamptothecin [45]. The AMPK-mTOR axis took part in NSCLC treatment by inhibiting cell proliferation, migration, invasion, and glycolysis and activating oxidative stress, autophagy, and apoptosis [46][47][48][49]. In the present study, RSV activated AMPK and mTOR by phosphorylation.…”
Section: Discussionsupporting
confidence: 50%
“…The impacts of RSV on the cell viability of human lung adenocarcinoma A549 cells and human bronchial epithelial BEAS-2B cells were evaluated by MTT assay. Two cell lines were treated with corresponding RSV concentrations (0, 5, 10, 20, 40, 60, 80, 100, 120, 140, 160, 180, and 200 µM) and duration (12,24,48, and 72 h) to select the appropriate treatment conditions. The results showed that lower concentration (5-20 µM) or shorter duration (12 h) of RSV treatment promoted cell viability of both A549 and BEAS-2B cells, compared with the control group.…”
Section: The Effect Of Rsv On Cell Viability In A549 and Beas-2b Cellsmentioning
confidence: 99%
“…Pro-inflammatory factors and immune-related factors also play different roles in the process of tumor metastasis. For example, mitochondrial reactive oxygen species (ROS) can further affect tumor metastasis by regulating the inflammatory response [ 39 41 ]. Thus some natural antioxidants or anti-inflammatory drugs may also be used to inhibit tumor metastasis [ 39 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, mitochondrial reactive oxygen species (ROS) can further affect tumor metastasis by regulating the inflammatory response [ 39 41 ]. Thus some natural antioxidants or anti-inflammatory drugs may also be used to inhibit tumor metastasis [ 39 , 42 , 43 ]. In colorectal cancer, including the spectrum from normal colorectal adenoma to cancer, infiltrating macrophages display high levels of Wnt2 and Wnt5a.…”
Section: Discussionmentioning
confidence: 99%
“…Various preclinical studies have indicated that metformin can suppress cell proliferation, trigger apoptotic cell death, provoke cell cycle arrest in vitro , and diminish the occurrence and growth of tumors in an in vivo orthotopic or xenograft mouse model system ( Buzzai et al ., 2007 ; Ben Sahra et al ., 2008 ; Zhao et al ., 2015 ; Zi et al ., 2015 ). Metformin can be used as a sensitizer or can be combined with standard chemo-therapeutic agents and radiotherapy to treat tumors ( Fasih et al ., 2014 ; Qu et al ., 2014 ; Zhang et al ., 2014 ; Lengyel et al ., 2015 ; Uehara et al ., 2015 ; Zhu et al ., 2021 ). Furthermore, metformin plays an important role in targeting tumor stem cells and in reverting the epithelial-mesenchymal transition, a key process in tumor metastasis ( Barriere et al ., 2013 ; Nangia-Makker et al ., 2014 ; Lei et al ., 2017 ).…”
Section: Introductionmentioning
confidence: 99%